2021
DOI: 10.1186/s40168-020-00978-8
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence patterns of soil methanogens are closely tied to methane generation and community assembly in rice paddies

Abstract: Background Soil methanogens participate in complex interactions, which determine the community structures and functions. Studies continue to seek the coexistence patterns of soil methanogens, influencing factors and the contribution to methane (CH4) production, which are regulated primarily by species interactions, and the functional significance of these interactions. Here, methane emissions were measured in rice paddies across the Asian continent, and the complex interactions involved in coex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(33 citation statements)
references
References 81 publications
2
25
1
Order By: Relevance
“…Furthermore, combined with network analysis, we suggested that microbial coexistence is more widespread under weaker environmental filtering. Several studies attempted to unveil the assembly and coexistence mechanisms in microbial ecology ( Liu et al, 2020 ; Zhu et al, 2020 ; Li et al, 2021 ), and a similar trend resembling the present study was also reported in agricultural soil ecosystems ( Jiao et al, 2020 ).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Furthermore, combined with network analysis, we suggested that microbial coexistence is more widespread under weaker environmental filtering. Several studies attempted to unveil the assembly and coexistence mechanisms in microbial ecology ( Liu et al, 2020 ; Zhu et al, 2020 ; Li et al, 2021 ), and a similar trend resembling the present study was also reported in agricultural soil ecosystems ( Jiao et al, 2020 ).…”
Section: Discussionsupporting
confidence: 86%
“…As expected, CRT, representing the rare species that might be favored occasionally ( Caron and Countway, 2009 ; Konopka et al, 2015 ), were more easily controlled by deterministic processes of community assembly (mainly variable selection in this study) in response to changing environments. Li et al (2021) applied a phylogenetic null model and network analysis to examine the direct and/or indirect cooperation between methanogenic archaeal taxa in rice paddies across the Asian continent, and they demonstrated that the relative importance of determinism and stochasticity differed between commonly coexisted taxa and endemically coexisted taxa. Similarly, Mo et al (2020) investigated the biogeography and co-occurrence patterns of marine bacteria from three subtropical bays, and they found that deterministic processes played a greater role in the community variation of specialists (84%) compared with generalists (56%).…”
Section: Discussionmentioning
confidence: 99%
“…The dominant taxa were Methanosaeta, Methanomoicrobiales, and Methanoculleus, compared with Methanosaeta and Methanosarcina with a significant increase in Methanosarcina from 5.01% at 7D to 41.21% at 18D and a decrease in Methanosaeta from 45.36% to 39.82%, Methanomicrobiales (from 20.34% to 3.96%), and Methanoculleus (from 17.87% to 6.49%). In the AD process, Methanosarcina and Methanosaeta can directly utilize acetate formed by acetogenic bacteria [38]. Methanosaeta is an obligate acetolytic methanogen and has a higher competitiveness of acetate compared with Methanosarcina [39].…”
Section: Archaeal Community Characteristicsmentioning
confidence: 99%
“…Some of them only use one pathway, while the others can utilize two (Godin et al, 2012). The complex interactions of soil methanogenic communities influence wetland ecosystem structures and functions (Deng et al, 2012;Li et al, 2021). A previous study found that the coexistence patterns of soil methanogenic communities in rice paddies are closely associated with their function, and their complex interactions may contribute more to soil functions, compared with species diversity (Li et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The complex interactions of soil methanogenic communities influence wetland ecosystem structures and functions (Deng et al, 2012;Li et al, 2021). A previous study found that the coexistence patterns of soil methanogenic communities in rice paddies are closely associated with their function, and their complex interactions may contribute more to soil functions, compared with species diversity (Li et al, 2021). Thus, an understanding of methanogenic interspecies interactions in complex microbial ecosystems is essential for recognizing both sharing and competition among methanogens in similar trophic niches (Kato et al, 2014).…”
Section: Introductionmentioning
confidence: 99%